SETTLEMENT OF THE CONFLICT ON THE BORDERLINE OF THE RICE FIELDS VILLAGE WITH THE VILLAGE OF SUNGAI JALAU KAMPAR UTARA DISTRICT, KAMPAR REGENCY - Birman Simamora; Eddy Asnawi; Andrizal (Jurnal Cakrawala Ilmiah, 2023)
There are many problems overlapping village boundaries between one village and another. It is easy for the village government to exercise authority in village management if the boundaries of the village area are well defined. Villages must have regional boundaries and authority without regional boundaries will cause various problems in the area, one of which can be conflicts between one village and another. The problems in this study are: First, what are the causes of boundary conflicts between Sawah Village and Sungai Jalau Village? Second, What is the Impact of the Boundary Conflict between Sawah Village and Sungai Jalau Village on the Community? Third, How to resolve boundary conflicts between Sawah Village and Sungai Jalau Village?The aims of this research are: To explain the causes of boundary conflicts between Sawah Village and Sungai Jalau Village; To explain the impact of boundary conflicts between Sawah Village and Sungai Jalau village on the village community and government; To explain the resolution of boundary conflicts between Sawah village and Sungai Jalau village. The research method used is this type of research is sociological law. Sociological legal research is more directed at a study that discusses the enactment of positive law and its influence on people's lives as well as the influence of non-legal factors on the formation of legal provisions. This study uses a juridical approach, to find out and explain the causes of boundary conflicts between paddy fields and Sungai Jalau Village, North Kampar District, Kampar Regency.Conclusion:1. Settlement of the boundaries between Sawah Village and Sungai Jalau Village, North Kampar District, Kampar Regency is carried out in accordance with applicable legal regulations, namely in Article 9 of the Minister of Home Affairs Regulation Number 45 of 2016 concerning Determination and Confirmation of Village Boundaries, it is stated that boundary disputes between villages in one sub-district it was resolved by deliberation facilitated by the North Kampar Sub-District Head.2. The impact of the border conflict between Sawah village and Sungai Jalau village, North Kampar sub-district, Kampar regency resulted in many obstacles to completing village government administration, for example, there are many land transactions that have not been able to transfer the name in their SKGR because the village government feels doubtful if they issue a letter. land that is not included in the jurisdiction of the government.3. The boundary conflict between Sawah village and Sungai Jalau village had not been resolved until the research was carried out because several deliberations had been held facilitated by the sub-district head but had not reached a consensus regarding the boundaries of the two villages. Active coordination from the sub-district government is a way to strengthen communication between community leaders as one of the elements that is expected to facilitate the settlement of the boundaries of the two villages.SuggestionThe efforts of the North Kampar District Government in resolving the border conflict between Sawah village and Sungai Jalau village are suggested as follows1. The Kampar Utara District Government must hold ongoing and routine deliberations to discuss the resolution of the border conflict between the two villages, the District Government must refer to the basis for the division of Sungai Jalau village by meeting or holding meetings with community leaders, providing understanding to each figure the people of the two villages about the importance of prioritizing the interests of the community over their own interests, in the sense of the interests of the village itself.The sub-district government should form a special team to deal with boundary conflicts between Sawah village and Sungai Jalau village, so that sub-district activities are not disrupted, but must remain under the supervision of the sub-district government, facilitating ongoing meetings or meetings to discuss resolving the border conflicts between the two villages . The sub-district government must be able to make firm decisions without having to listen to various arguments from each village that impose their wishes for the public interest.